Diabetes mellitus and atrial remodelling in patients with paroxysmal atrial fibrillation: Role of electroanatomical mapping and catheter ablation. (May 2018) - Grieco, Domenico; Palamà, Zefferino; Borrelli, Alessio; De Ruvo, Ermenegildo; Sciarra, Luigi; Scarà, Antonio; Goanta, Emilia; Calabrese, Vito; Pozzilli, Paolo; Di Sciascio, Germano; Calò, Leonardo
Complex fractionated atrial electrograms (CFAEs) are related to atrial fibrosis, but their ablation has not yet shown superiority. The aim of the study was to compare, in terms of clinical outcome, two strategies of paroxysmal atrial fibrillation (AF) ablation in patients with type 1 diabetes mellitus (DM): pulmonary vein isolation (PVI) vs. PVI + CFAEs. Compared to an historical population of patient with paroxysmal AF and without DM, a higher percentage of patients with DM showed more than 25% of atrial area interested by CFAEs (study population, 58% vs historical group, 15%; p < 0.05). In PVI group, recurrences rate was similar in patients with HbA1c ⩽ 7.5% vs HbA1c > 7.5% (30% vs 22%; p = not significant), but a greater AF burden was observed in patients with HbA1c > 7.5% (6 ± 2 vs 1 ± 2; p < 0.05). In hazard ratios analysis PVI+CFAEs seems more effective than PVI alone in patients with HbA1c > 7.5% (hazard ratio, 1.28; p < 0.05), more than 25 years from DM diagnosis (hazard ratio, 1.25; p < 0.05) and more than five AF episodes/year (hazard ratio, 1.2; p < 0.05). Type 1 DM patients had complex atrial 'substrate', as documented by wider CFAEs areas. Despite this, 1-year follow-up recurrence rate was similar between two ablation approaches (PVI 27% vs. PVI+CFAEs 21%; p = not significant). In our study, only specific subgroups, like patients with disglycaemic state (HbA1c > 7.5%), long diabetes mellitus history and high AF burden, benefit from PVI+ CFAEs approach.